Destabilizing the gaze towards male fashion models: Expanding men's gender and sexuality identities. Issue 1 (1st March 2016) - Barry, Ben; Phillips, Barbara
Fashion advertisements pioneered the mainstream objectification of the male body in popular culture. While scholars have theorized about the influence of these images on men, few empirical studies have examined men's engagement with them. This study investigates how men experience objectified men's fashion advertisements through interviews with 30 gay and straight male fashion consumers. Analysis revealed that both gay and straight men gaze upon images through the lenses of appreciation and fantasy, destabilizing normative binaries of gender and sexuality. Despite the delight that men experienced, objectified fashion images roused despair and distress because the models represented limited body ideals and expressions of gender and sexuality. Findings provide empirical evidence to support and advance a new theorization of the male gaze in men's fashion images. Fashion professionals are advised to expand their representations of male imagery to enable men to continue to traverse gender and sexuality boundaries.